Do You Feel the Same as I Do? Differences in Virtual Reality Technology Experience and Acceptance Between Elderly Adults and College Students - Liu, Qian; Wang, Yanyun; Tang, Qingyang; Liu, Ziwei (Frontiers in Psychology, 2020)
Virtual reality (VR) has been widely applied in medical health areas and the entertainment and tourism industries, in which elderly people are a primary target. However, most studies on VR have focused on how people respond to this new technology and its effects on younger generations. Our study explored the differences in VR experience and acceptance between elderly adults and college students. A mixed method approach including both experiments and in-depth interviews was applied in this study. Our results show that elderly adults reported a higher level of telepresence and stronger emotional responses than young adults in VR viewing regardless of the VR device. The ways in which elderly people processed and evaluate VR content and devices were different from those of young people. Elderly people reported more positive attitudes toward the video they watched than young people, but this did not necessarily lead to more positive attitudes toward the viewing experience.